Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan - Mhd. Shafwan Aziz; Rizqy Fadhlina Putri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to describe the results of a financial ratio analysis conducted at PT RUMAH KREATIF TEKNOLOGI. This financial ratio analysis includes liquidity, solvency, and profitability ratios. Quantitative methods were used in this study. Secondary data served as the source of information. The focus of the study was the financial statements of PT RUMAH KREATIF TEKNOLOGI, including the balance sheet and income statement from 2020 to 2024. Information regarding PT RUMAH KREATIF TEKNOLOGI was taken from the official website of the Indonesia Stock Exchange (IDX). Based on the collected data, it was concluded that PT RUMAH KREATIF TEKNOLOGI exhibited a consistently good Debt-to-Equity Ratio (DER) Solvency Ratio, never experiencing any negative changes, remaining below 100%.